Relative Importance Index (RII) in Ranking the Factors of Employer Satisfaction Towards Industrial Training Students - Duratul Ain Tholibon; Masyitah Md Nujid; Hamizah Mokhtar; Jamilah Abd Rahim; Nurul Faiizin Abdul Aziz; Amirah Amalina Ahmad Tarmizi (Research and Education Development (READ) Institute collaborate with Faculty of Education and Teacher Training of IAIN Palopo, 2021)
This study aims to examine the level of employer satisfaction towards industrial training students of the UiTM Pahang Civil Engineering Diploma Program and identify employer satisfaction factors for industrial training students from aspects of knowledge, personality, generic skills, and soft skills. This study is focused on semester four students undergoing industrial training. This study was conducted on 158 respondents from various organizations. Using the important relative index (RII), the level of important factors was ranked through the value of the index. Findings show the highest employer satisfaction is towards the student mastering their knowledge, adhering to the working hours, improving their skills and knowledge, and communicating well with co-workers. Besides, it also shows a good correlation between knowledge and personality among industrial training students. This study found that industrial training students of the Civil Engineering Diploma Program had a good level of control over all four domains. Overall findings showed that employers are satisfied with the industrial training students of the UiTM Pahang Civil Engineering Diploma Program. This study is important to measure the effectiveness of the industrial training syllabus in terms of achieving the program outcomes addressed in the syllabus